NONSTANDARD FINITE DIFFERENCE METHOD OF MODELLING ZOONOTIC DISEASES. (2022) - OTOO, DOMINIC; OSMAN, SHAIBU; TOGBENON, HOUENAFA ALAIN; ONSONGO, WINNIE MOKEIRA; GODJO, THIERRY GORLON; MAKINDE, OLUWOLE DANIEL
No abstract available